Interação genótipos por ambientes, adaptabilidade e estabilidade de genótipos de soja em verão e híbridos de milho em safrinha - Mijone, Ana Paula (2018)
The interaction genotypes by environments (G x E) influences the breeding process, especially for indication and recommendations of cultivars. In this perspective, the purpose of this study was to evaluate the yield performance, adaptability and stability of soybean cultivars grown in the 2016/17 and 2017/18 season and safrinha corn cultivated in the 2015/16 and 2016/17 season in traditional and non-traditional regions for safrinha; and to determine the adaptability and stability of the materials by parametric, non-parametric and multivariate methods. For both crops, statistical analyzes were performed in the Genes and Estabilidade Program and the Lin and Binns (1988) methods modified by Carneiro (1998), Eberhart and Russel (1966), Centroid and the AMMI method were evaluated. In the 2016 season, 24 hybrids were evaluated in 7 environments; in 2017 season 13 hybrids were evaluated in 6 environments. The environments were located between the regions of Southwest of Goiás, Southeast of Goiás, Triângulo Mineiro and Alto Paranaíba and Northwest of Minas. It was verified existence of G x E interaction for the seasons, as well as the predominance of interaction decomposition of the complex type. It was observed that in the two seasons, the sites considered as traditional in maize cultivation in safrinha, Jataí-GO and Montividiu-GO favored the productive performance of the hybrids, whose averages were higher than the national productivity averages of 3859 kg ha-1 in 2016 and 5562 kg ha-1 in 2017.It is concluded that the G x A interaction for grain yield of maize hybrids grown in safrinha is complex; that for the 2016 season, which presented high grain yield, wide adaptation and high stability was the hybrid AG8700PRO3; and for the 2017 season it was the hybrid AS1757PRO3. The soybean experiments were carried out in the 2016/2017 and 2017/2018 season in seven locations located in the states of Goiás and Minas Gerais. Eighteen soybean genotypes were evaluated, with eight lines developed by soybean breeding program and eight commercial checks: BMX Desafio RR, BMX Flecha IPRO, Maradona-Anta82, AS3680IPRO, M7110IPRO, M6972IPRO, M7198IPRO, AS3730IPRO, M7739IPRO, TMG 7062 IPRO. Genotype environment interaction was verified by significant and complex. The genotypic coefficient for yield was of high magnitude, whose estimate was 95.23%. The genotypes that presented the highest yields were Soy-13, Soy-03, Soy-11, Soy-09 and Soy-10. It is concluded that according to the analyzes of the methods Lin and Binns (1988) modified by Carneiro (1998), Eberhart and Russel (1966) and AMMI method, the Soy-09 Genotype presented high grain yield, wide and high adaptation stability.